Effect of CYP3A4 metabolism on sex differences in the pharmacokinetics and pharmacodynamics of zolpidem - Seonghae Yoon; Seongmee Jeong; Eben Jung; Ki Soon Kim; Inseung Jeon; Yujin Lee; Joo-Youn Cho; Woo-Yong Oh; Jae-Yong Chung (Scientific Reports, 2021)
Abstract To investigate pharmacokinetic and pharmacodynamic differences of zolpidem between males and females and their causes, including CYP3A4 activity. A single oral dose of zolpidem (10 mg) was administered to 15 male and 15 female healthy subjects. Blood samples were collected up to 12 h post-dose to determine plasma zolpidem concentrations. Pharmacokinetic parameters were obtained using non-compartmental analysis. Digit symbol substitution test, choice reaction time, and visual analog scale of sleepiness were used to evaluate pharmacodynamics. We measured CYP3A4 activity using 4β-hydroxycholesterol, an endogenous metabolite. Mean maximum plasma concentration and area under the plasma concentration–time curve were higher for females than for males (9.9% and 32.5%, respectively); other pharmacokinetic parameters showed no significant differences. Pharmacodynamic scores for females showed delayed recovery compared with that for males. CYP3A4 activity was higher in females than in males (p = 0.030). There was no serious adverse event, and adverse event incidence was not different between the sexes. Zolpidem exposure was about 30% higher in females than in males. Delayed pharmacodynamic score recovery in females could be related to higher zolpidem concentrations. Although apparent clearance was lower in females, systemic clearance might not be the cause of the different exposures to zolpidem.